Chloroplast Genome Draft of Dryobalanops aromatica Generated Using Oxford Nanopore Technology and Its Potential Application for Phylogenetic Study - Dwi Wahyuni (MDPI AG, 2021)
Kapur (Dryobalanops aromatica) is an important dipterocarp species currently classified as vulnerable by the IUCN Red List Threatened Species. Science-based conservation and restoration efforts are needed, which can be supported by new genomic data generated from new technologies, including MinION Oxford Nanopore Technology (ONT). ONT allows affordable long-read DNA sequencing, but this technology is still rarely applied to native Indonesian forest trees. Therefore, this study aimed to generate whole genome datasets through ONT and use part of these data to construct the draft of the chloroplast genome and analyze the universal DNA barcode-based genetic relationships for D. aromatica. The method included DNA isolation, library preparation, sequencing, bioinformatics analysis, and phylogenetic tree construction. Results showed that the DNA sequencing of D. aromatica resulted in 1.55 Gb of long-read DNA sequences from which a partial chloroplast genome (148,856 bp) was successfully constructed. The genetic relationship was analyzed using two selected DNA barcodes (rbcL and matK), and its combination showed that species of the genus Dryobalanops had a close relationship as indicated by adjacent branches between species. The phylogenetic tree of matK and the combination of the matK and rbcL genes showed that D. aromatica was closely related to Dryobalanops rappa, whereas the rbcL gene showed group separation between D. aromatica and D. rappa. Therefore, a combination of the matK and rbcL genes is recommended for future use in the phylogenetic or phylogenomic analysis of D. aromatica.